Imaging the Southern Sky An Amateur Astronomer's Guide - Chadwick, Stephen; Cooper, Ian (The Patrick Moore Practical Astronomy Series,, 2012)
"If you're looking for a handy reference guide to help you image and explore the many splendors of the southern sky, Imaging the Southern Sky is the book for you. The work features not only stunning color images, all taken by Stephen Chadwick, of the best galaxies, nebulae, and clusters available to astrophotographers, but also lesser-known objects, some of which have gone largely unexplored! Beginners and experienced observers alike should appreciate the book's remarkable imagery and simple text, which provides concise and accurate information on each object and its epoch 2000.0 position, and also expert testimony on its visual nature. Each object essay also includes a section on technical information that should help astrophotographers in their planning, including telescope aperture, focal length and ratio, camera used, exposure times, and field size. As a charming bonus, the authors have taken the liberty to name many of the lesser-known objects to reflect their New Zealand heritage. Constellation by constellation, from Apus to Volans, Imaging the Southern Sky explores the night sky in a way that should appeal to sky lovers of all ages." - Stephen J. O'Meara.